ACUTE AND SUB ACUTE TOXICITY STUDIES OF A SIDDHA SASTRIC FORMULATION LINGA CHENDHURAM IN WISTAR RATS - Elansekaran, *S.; Thanigavelan, V.; Logamanian, M. (International Journal of Ayurveda and Pharma Research, 2016)
Linga Chendhuram (LC) is a herbo-mineral formulation cited in Siddha literature Siddha Vaithiya Thirattu comprises of purified Lingam (Cinnabar) processed in herbal juice – Citrullus colocynthis and used in the management of various types of fever, arthritis and anaemia at 65 mg/dose. Acute and Sub-acute oral toxicity of Linga Chendhuram was carried out in Wistar rats under OECD guidelines 423 and 407. In acute study, LC was administered at 2000mg/kg orally and animals were observed for toxic signs for 14 days. In sub-acute toxicity study, test groups were treated with LC at 18, 90 and 180 mg/kg/day along with 2 ml of diluted honey and control group with distilled water 2 ml/day for 28 days daily. LC at 2000mg/kg produced no treatment related toxic signs or mortality during the study. Haematological and biochemical parameters were analyzed using auto analyzer with standard kits and one way ANOVA followed by Dunnett test was performed for significant analyses. Gross necropsy and histopathology studies using H&E stain were done on major organs. LD50 was found more than 2 g/kg. No-Observed-Adverse-Effect level of LC was seen at 180 mg/kg in 28 days of treatment. No abnormal findings were noted in high dose group organs. Administration of LC at its human therapeutic dose of 195 mg/kg in rat (180 mg/kg) is safe.